Dual role of ACE2 in regulating inflammation triggered by Omicron S1 and other SARS-CoV-2 Spike variants - Pedoto, Annamaria; Lozano-Gil, Juan M.; Ocaña-Esparza, María; Conesa-Hernández, Ana M.; Candel, Sergio; Cayuela, María L.; Mulero, Victoriano; Tyrkalska, Sylwia D. (Frontiers in Immunology, 2026)
Since the emergence of SARS-CoV-2 in late 2019, substantial efforts have been made to understand its mechanisms of pathogenicity. Although angiotensin-converting enzyme 2 (ACE2) has been identified as the main receptor for viral entry, the complexity of the host immune response to different Spike protein conformations and variants remains poorly understood. Using zebrafish larvae as an in vivo model, we show that the monomeric S1 domain of the Omicron variant triggers a potent proinflammatory response characterized by elevated Nfkb activity and increased expression of key cytokines, despite reduced recruitment and expansion of neutrophils and macrophages. Notably, monomeric S1 Omicron also promotes neutrophil cell death, suggesting an alternative mechanism of immune modulation. In contrast, the trimeric form of the Spike protein fails to induce significant inflammation or emergency hematopoiesis, likely due to its efficient neutralization by endogenous Ace2. Our results revealed that both zebrafish and human ACE2 exert a dual anti-inflammatory role: indirectly through the production of angiotensin-(1-7), and directly by binding and neutralizing the trimeric Spike. These results provide new insights into variant-specific immune responses and the multifaceted role of ACE2 in modulating SARS-CoV-2-induced cytokine storm syndrome.